The Structural Complexity and Animal Tissue Distribution of N-Glycolylneuraminic Acid (Neu5Gc)-Terminated Glycans. Implications for Their Immunogenicity in Clinical Xenografting - Breimer, Michael E.; Holgersson, Jan (Frontiers in Molecular Biosciences, 2019)
N-Glycolylneuraminic acid (Neu5Gc) terminated glycans are present in all animal cells/tissues that are already used in the clinic such as bioprosthetic heart valves (BHV) as well as in those that potentially will be xenografted in the future to overcome end stage cell/organ failure. Humans, that lack this antigen determinant, can react with an immune response after exposure to Neu5Gc present in these products/cells/tissues. Genetically engineered donor source animals lacking Neu5Gc has been generated and so has animals that in addition lack the major Gal xenoantigen. The use of cells/tissues/organs from such animals may improve the long-term performance of BHV and allow future xenografting. This review summarizes the present knowledge regarding structural complexity and tissue distribution of Neu5Gc on glycans of cells/tissue/organs already used in the clinic or intended for treatment of end stage organ failure by xenografting. In addition, we briefly discuss the role of anti-Neu5Gc antibodies in the xenorejection process and how knowledge on Neu5Gc structural complexity can be used to design novel diagnostics for anti-Neu5Gc antibody detection.